The influence of Tariqa in the Tablighi Jama'at Congregation: Principles and Practice - Ilyas, M. Azizzullah (UIN Fatmawati Sukarno Bengkulu, 2022)
Tablighi Jamaat movement has several proselytizing agendas that are not explicitly stated but can be seen from the phenomenon of the Tablighi Jama'ah ritual practice, which in some aspects carries the values of tariqa and Sufism. The research was conducted to analyze the tariqa and Sufi elements in the Da'wah of the Tablighi Jama'at. This research is qualitative with participatory observation data sources interviews and enriched with library data. The snowball technique selects the sample of informants. The data obtained were collected, grouped, and analyzed for further description descriptively. The study results found the Tablighi Jamaat had practices sourced from the congregation's methods. The Chistiyah Order is the dominant order reference principles and practices. Another order that also influenced was the Naqhsabandiyah. For the Syadziliyah congregation, there are similarities in zikr and far away, but further analysis is needed. Meanwhile, the Naqhsabandiyah-Khalidiyah later influenced the Tablighi Jamaat in Indonesia.